PENERAPAN DATA MINING UNTUK MENGOLAH TATA LETAK BUKU DENGAN METODE ASSOCIATION RULE - Alfannisa Annurullah Fajrin (Teknik Informatika, 2018)
Data Mining is the development or discovery of new information by looking for certain patterns or rules from a large amount of data that is expected to overcome the existing problems data processing utilizes the data of borrowing transaction of book in the library ABC to be able to know which books are often borrowed, help to do preparation of book placement in accordance with the level of support and confidence so as to help the quality of service in the library better. This research uses association rule method and algorithm used by FP-Growth, microsoft excel database, and Rapidminer 5.3 to process data mining. The most important thing in data mining techniques is the rule for finding the highest frequency patterns between sets of itemsets. Data mining also has the goal to finding new knowledge frome processed data. Over last few decades, new methods have the ability to be developed around data collection and data generation. Data collection tools have provided us with large amounts of data.nthe data mining process has integrated techniques from various disciplines such as, statistics, learning technology database engine, pattern recognition, neural networks, information search and spatial analysis data. The mining engineering data has been used in such fields as bussines management, science, engineering, banking data management, administration, and many other applications.